Extreme Chemistry of Superheavy Elements - Nagame, Yuichiro; Sato, Tetsuya K. (Butsuri, 2023)
Superheavy elements (SHEs) with atomic numbers greater than 100 are expected to have interesting chemical properties that differ from those anticipated by the Periodic Table caused by strong relativistic effects. The SHEs must be produced in heavy-ion induced nuclear reactions and are only available on a single atom scale at a time. The difficulty of the experiments, therefore, still causes uncertainty about their chemical properties and remains things to be further investigated. In recent years, several fascinating studies have been reported: the atomic structure of lawrencium (Lr, element 103) by measuring the first ionization potential, co-precipitation of rutherfordium (Rf, element 104), the volatility of dubnium (Db, element 105) compounds, and formation of the hexacarbonyl compound of seaborgium (Sg, element 106). Here we briefly review recent highlighted results of chemical studies on SHEs. Future prospects of these challenging research subjects are briefly discussed.